2013
DOI: 10.1155/2013/186312
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features and Transcriptional Activity of Chicken PPARs (α,β, andγ)

Abstract: While an understanding of lipid metabolism in chickens is critical for a further improvement of food production, there are few studies concerning differences in lipid metabolism mechanisms between chickens and other species at a molecular level. Chickens have three PPAR gene subtypes (α, β, and γ) that function differently from those present in humans and mice. The chicken PPAR-gamma (cPPARγ) gene is shorter than that in humans and lacks a γ2 isoform. Moreover, in serum-free media, cPPARγ shows high transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although a considerable amount is known about the effects of CLA on PPAR γ transcription and on its downstream target genes in rodents and humans, there is a scarcity of data examining PPAR γ transcription and function in the chicken's adipose. PPAR γ gene is shorter than that in humans and lacks γ 2 isoform [ 2 ]. This may contribute to the differences observed in the lipid and glucose metabolism of chickens compared to mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a considerable amount is known about the effects of CLA on PPAR γ transcription and on its downstream target genes in rodents and humans, there is a scarcity of data examining PPAR γ transcription and function in the chicken's adipose. PPAR γ gene is shorter than that in humans and lacks γ 2 isoform [ 2 ]. This may contribute to the differences observed in the lipid and glucose metabolism of chickens compared to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Modern bird strains tend to accumulate excess fat [ 1 ]. This tendency has proven to be one of the main problems for poultry producers as it has a negative effect on the broiler industry today because excessive fat deposits result in lower meat yields [ 2 ]. There are evidences that the growth pattern of fat depots in chickens can be affected by dietary factors [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after, a rat version of PPAR α as well as three novel members related to each other (xPPAR α , xPPAR β , and xPPAR γ ) and to mouse PPAR α have been subsequently cloned from Xenopus (frog) [13]. Since then, substantial efforts have been made to identify other related receptors; several additional PPAR isoforms and variants have been therefore isolated in a wide range of species including mammals (human, rabbit, mouse, rat, pig, rhesus and cynomolgus monkey, dog, guinea pig, hibernating ground squirrel, and hamster), fishes (grass carp, cobia not only but also marine fish such as the teleost red sea bream ( Pagrus major ) and the mullet Chelon labrosus ), marine gastropod mollusks ( Cyclostoma ), reptiles (leopard gecko, crocodile, and turtle), and birds (domestic chicken, goose) [1451]. …”
Section: Introductionmentioning
confidence: 99%
“…It also showed that the enriched genes were mainly involved in pyruvate metabolism, glycolysis/gluconeogenesis, biosynthesis of antibiotics, PPAR, glutathione metabolism, and citrate cycle pathways (p < 0.05). Pyruvate metabolism pathway plays an important role in the synthesis of glucose from lactate and dihydroxyacetone in chicken liver [33]. Many studies have reported that under any kind of stress, the chicken liver plays a significant role in maintaining homeostasis through glycolysis/Gluconeogenesis pathways [17,34,35].…”
Section: Discussionmentioning
confidence: 99%